Nutritive Value And Bioavailability Of Protein Feedstuffs For Broiler Chickens - Lim, Fairda (1985)
Three experiments were conducted to evaluate the nutritive value and biological availability of nutrients in proteinaceous feedstuffs for broiler chickens. These include Thai fish meal ( FSM ) , Peruvian FSM, China soybean meal ( SBM ) , two locally-processed SBM , Federal Flour Mill ( FFM ) and Soon Soon ( SS ) , respectively, and single-cell protein "Pruteen" . In Experiment 1 , the nutritive values of these feedstuffs were subjected to the following chemical analyses: proximate, minerals, detergent fibre, amino acids and in vitro digestibility . Crude protein ( CP ) contents of fish meals ( on dry matter basis ) were 54.17% for Thai F SM and 60.98 % f or Peruvian FSM . Ash content in Thai FSM was higher ( 25.86%) than Peruvian FSM (15.51%). Gross energy in Peruvian F SM (4,488 kcal /g ) was higher than Thai FSM (3,781 kcal/g) , attributing mainly to higher fat content in the Peruvian FSM (10.37%) than in the Thai FSM (7.59%) . In vitro evaluation of fish meals showed that the digestible CP (DCP ) was higher for Thai FSM ( 4 2 . 2 % ) than the Peruvian FSM ( 40.0%) . SBM of China origin showed highest protein content (44.41%) followed by FFM SBM (43 . 09%) and SS SBM (41.04%) . However , the amino acid profile s showed that China SBM had the lowest total amino acid value (42.81%) and SS the highest (44.08%) . In vitro evaluation showed that China SBM had the highest DCP (38.33%) and that of the two locally-processed SBM were comparable (35.15and 35.64% ) . Pruteen had a high CP value (71.94%) and DCP (61.0%) , but low in crude fibre (/ 1 %) , and high in gross energy (4,527 kcal /g ) .